Spectral variability and reverberation time delays in the Suzaku X-ray spectrum of NGC 4051 - Miller, L; Turner, T; Reeves, J; Lobban, A; Kraemer, S; Crenshaw, D (2009)
Long-exposure Suzaku X-ray observations of the active galaxy NGC 4051 from 2005 and 2008 are analysed, in an attempt to reach a self-consistent understanding of the spectral variability on long timescales and at high time resolution. Principal components analysis and a maximum likelihood method of power spectrum analysis are used. In common with other type I AGN, the spectral variability is dominated by a varying-normalisation power-law component together with a quasi-steady, hard-spectrum offset component that contains Fe K atomic features. NGC 4051 displays a strong excess over a power-law at energies above 20 keV, some fraction of which also appears to vary with the power-law continuum. The fast-timescale power spectrum has a shape consistent with previous determinations, but significant differences are found between the low and high flux states of the source, demonstrating that the power spectrum is non-stationary. Frequency-dependent time lags between the hard and soft bands of up to 970+/-225s are measured. The existence of the observed lags excludes the possibility that the hard spectral component originates as reflection from the inner accretion disk. We instead show that the frequency- and energy-dependent time lags may be explained as reverberation, caused by reflection from a thick shell of material with maximum lags of about 10,000s. If the reflecting material surrounds the AGN, it extends to a distance about 1.5x10^14 cm, 600 gravitational radii, from the illuminating source and the global covering factor is C(g) >~ 0.4, confirming suggestions that type I AGN have high covering factors of absorbing and reflecting material. Given the spectral and timing similarities with other type I AGN, we infer that this structure is common in the type I population. [abridged]